Peran Managemen Agar Meningkatkan Pendidikan Bermutu di Era Digital - Anggie Natasya Putri; Aninda Rahma Melani; Syifa Rahma Nabila (Pusat Riset dan Inovasi Nasional, 2023)
The role of management in improving the quality of education in the digital era aims to plan education that is fair, of high quality, effective and responsible, and enhances the positive image of education. The research process aims to provide knowledge about the need for management in educational organizations. Researchers used a descriptive-qualitative method by relying on library research or library research. Data collection was then analyzed using descriptive-analytical techniques, this analysis process involved review and evaluation. Management is a valuable element of an organizational institution that manages a life with the hope that it can run smoothly without obstacles. The urgency of improving the quality of education in the digital era includes the quality of student learning, supporting the government's independent learning program. There are challenges and obstacles to education management, namely the lack of educator skills in dealing with the digital era, security threats such as data hacking. Management, quality, education, digital, and challenges.